Demographic and clinical factors predicting retention in methadone maintenance: results from an Irish cohort. (May 2016) - Darker, C.; Ho, J.; Kelly, G.; Whiston, L.; Barry, J.
Abstract Background Retention in Methadone Maintenance Treatment (MMT) is superior to that of other therapies for opioid addiction, but with international retention rates around 50 % after 1 year of treatment, there remains a need for improved retention rates. Aims This study aimed to explore the demographic and clinical factors predicting retention in MMT. Methods Face-to-face surveys with MMT patients in a Dublin methadone clinic were conducted. Retention was assessed by the presence and duration of breaks in treatment at any stage. Results 189 patients participated in the study. 46 % (n  = 87) reported having at least one break in treatment, and the median duration of a break was 3 months. Age, current methadone dose and prescription of antipsychotic medication were significant predictors of retention. Patients who were older, single, living in their own home, on a higher dose of methadone, or taking antipsychotic medications had fewer breaks in treatment. Males tended to have significantly longer breaks. Patients reported that the main reasons for breaks were relapse into drug use (21.8 %, n  = 19), incarceration (11.4 %, n  = 10), weary of MMT (13.7 %, n  = 12) or problems at the clinic (10.3 %, n  = 9). Factors enabling regular attendance included wanting to get or stay clean (37.5 %, n  = 51), avoidance of withdrawal symptoms (16.1 %, n  = 22), methadone dependence (13.9 %, n  = 19) and services provided (10.2 %, n  = 14). Conclusion Patients who were older, single, living in their own home, on a higher dose of methadone, or taking antipsychotic medications had fewer breaks in treatment.